Is Cardiopulmonary Fitness Level a Risk Factor in Young Saudi Females? - Lubna I. Al Asoom (Journal of King Abdulaziz University: Medical Sciences, 2023)
Low physical fitness is one of the all-cause mortality risk factors. This study aims to estimate cardiopulmonary fitness (VO2 max) in young Saudi females and correlate it to anthropometric and hemodynamic parameters. Forty-eight young Saudi females completed an exercise stress test until exhaustion. Basal and maximum pulse rate, arterial blood pressure, VO2max and other anthropometric data were measured. The population was divided into low and high VO2 max groups and a comparison was run using student t-test. Correlation was tested between VO2 max and other measured parameters. The mean VO2 max of the sample population was low (33.6 ± 8.2 mL/ (kg min) with 37.5% exhibiting fair to very poor VO2 max value. The low VO2 max group was characterized by higher body mass index, exercise diastolic and mean arterial blood pressure when compared to normal VO2 max group, indicating a strong negative correlation. This study revealed a low cardiopulmonary fitness in young Saudi females and showed a strong association between VO2 max and increased body fat and maximum exercise diastolic blood pressure. These findings provide reliable indicators of increased all-cause mortality risk in young Saudi females and increase the urgency of prompt action.